2018
DOI: 10.1111/mec.14577
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome repeats tip the balance towards speciation

Abstract: Because sex chromosomes, by definition, carry genes that determine sex, mutations that alter their structural and functional stability can have immediate consequences for the individual by reducing fertility, but also for a species by altering the sex ratio. Moreover, the sex-specific segregation patterns of heteromorphic sex chromosomes make them havens for selfish genetic elements that not only create suboptimal sex ratios but can also foster sexual antagonism. Compensatory mutations to mitigate antagonism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 200 publications
(277 reference statements)
0
30
0
Order By: Relevance
“…The ancient tuatara, all crocodilians, a majority of turtles, and some lizards show TSD [8,180,181], whereas most snakes, many lizards, and some turtles exhibit GSD, and a continuum of differentiation between homomorphic and heteromorphic sex chromosomes within taxa is observed [14,182]. Heteromorphic sex chromosomes show accumulation of satellites and amplification of microsatellites or telomeric repeats on Y or W sex chromosomes in many reptilian species and other amniotes [20,45,[183][184][185]. In some reptiles the sex chromosome contains no significant enrichment of repeats [185], whereas minimally differentiated XY chromosomes are observed in three cryptodiran turtles (Staurotypus crassicollis, S. triporcatus, and S. salvinii), in which the Y chromosomes are smaller than the X chromosomes owing to a difference in the copy number of 18S-28S rRNA genes [26,118].…”
Section: Repeats With Sex Chromosomes In Relation To An Ancestral Amnmentioning
confidence: 99%
“…The ancient tuatara, all crocodilians, a majority of turtles, and some lizards show TSD [8,180,181], whereas most snakes, many lizards, and some turtles exhibit GSD, and a continuum of differentiation between homomorphic and heteromorphic sex chromosomes within taxa is observed [14,182]. Heteromorphic sex chromosomes show accumulation of satellites and amplification of microsatellites or telomeric repeats on Y or W sex chromosomes in many reptilian species and other amniotes [20,45,[183][184][185]. In some reptiles the sex chromosome contains no significant enrichment of repeats [185], whereas minimally differentiated XY chromosomes are observed in three cryptodiran turtles (Staurotypus crassicollis, S. triporcatus, and S. salvinii), in which the Y chromosomes are smaller than the X chromosomes owing to a difference in the copy number of 18S-28S rRNA genes [26,118].…”
Section: Repeats With Sex Chromosomes In Relation To An Ancestral Amnmentioning
confidence: 99%
“…Patten () summarizes the growing empirical evidence for this model (including discoveries of cryptic X‐linked drivers that also cause incompatibility in hybrids) while emphasizing the contribution of the X to speciation via other forms of intragenomic conflict (including sexual and parental antagonism). Building on this theme, O'Neill and O'Neill () discuss the myriad ways selfish evolution of the sex chromosomes compromises genomic stability. Focusing on mammals, the authors describe several examples of rapidly diversifying copy number variants in repetitive DNAs on the sex chromosomes that could contribute to reproductive isolation.…”
Section: Faster Evolution Of Sequencesmentioning
confidence: 99%
“…The effects of CNVs on speciation can also be indirect. Recently a study of several genera found that CNVs on sex chromosomes were responsible for rapid changes to the sex ratio (O'Neill & O'Neill, 2018). These changes happen very quickly, making them responsible for the development of hybrid incompatibilities if two populations are in allopatry, ultimately leading to speciation.…”
Section: Genome and Gene Duplicationsmentioning
confidence: 99%